Construction of an Electron Bridge in Polyoxometalates/Graphene Oxide Ultrathin Nanosheets To Boost the Lithium Storage Performance - Chang, Jia-Nan; Zhang, Mi; Gao, Guang-Kuo; Lu, Meng; Wang, Yi-Rong; Jiang, Cheng; Li, Shun-Li; Chen, Yifa; Lan, Ya-Qian (Energy & fuels, 2020)
Polyoxometalates (POMs), possessing multiple-electron redox ability, controllable size, and precise structure, hold much promise to be applied as anode materials in lithium-ion batteries (LIBs). However, the applications of them have been largely limited by the low conductivity and dissolution in an electrolyte. Herein, we report a series of covalently connected MnMo6–2NH2–GO ultrathin nanosheets (as thin as ∼1.1 nm), in which MnMo6–2NH2 as the electron sponge is covalently linked to graphene oxide and the covalent bond as the electron bridge is highly adventurous for battery applications. Specifically, MnMo6–2NH2–GO-2 presents a reversible capacity of 1143 mAh g–1 (0.1 A g–1) after 100 cycles, and the capacity retention is nearly 100% at 1000 mA g–1 over 500 cycles. In addition, it also shows excellent rate capability (301 mAh g–1 in 5 A g–1). This work paves a new way in designing POM-based novel electrode materials for high-performance LIBs.